Contemporary financial management - McGuigan, James R. (New York : Cengage Learning Asia Pte Ltd, 2009)
It provides a brief introduction to financial management as well as providing many worked- out spreadsheet examples to provide an even grater applications approach to financial management.
Part 1. Introduction -- Part 2. Determinant of Valuation -- Part 3. The Capital Investment Decision -- Part 4. The Cost of Capital, Capital Structure and Dividend Policy -- Part 5. Working Capital Management -- Part 6. Additional Topics in Contemporary Corporate Finance .
Includes index.
Keywords: BUSINESS ENTERPRISES